The Naming Problem in the Recognition of Psi-Encoded Visual Information: Analysis and Implications - Graboi, Dan (Journal of Scientific Exploration, 2025)
A consistent finding in experiments involving telepathic and clairvoyance phenomena is the difficulty of a receiver of visual psi information to name objects and symbols in what they receive. This deficit has been called “the naming problem” by Russell Targ. To gain insight into this issue, the perceptual and cognitive process used by receivers of telepathic and clairvoyant information is examined. Introspective and behavioral data are included in the examination. Factors are identified which contribute to the naming problem. The perception process of a receiver of psi-encoded visual information can be viewed as a form of perception like that in visual imagery but without effective high-level cortical involvement. Psi-encoded information in visual telepathy and clairvoyance is hypothesized to contain information that is decoded into low-level visual features, while higher-level information that organizes sensory information into specific object names and meanings – information known by the sender, or “agent” in telepathy – is absent. The fact that the same naming problem and similar introspective reports about received visual impressions are found in both telepathy and clairvoyance suggests that the data structure of the psi-encoded information in both forms of psi phenomena is identical.